Physico-Chemical Studies of Oil/Water Emulsions Stabilized by Different Surfactants - Pandey, I.P. (Asian Journal of Chemistry, 2010)
Emulsions of a large varieties have been prepared and studied by taking two immiscible liquids as internal and external phases with a number of surface active materials naturally occurring substances and finely divided solids as emulsifying agents. The results shown by cetyl alcohol which reduces the rate of coalescence significantly, and very stable emulsions were produced. The enhanced stability is due to the formation of a coherent strong interfacial film which works as a barrier preventing coalescence by virtue of its rheological properties.